Utilization of Fermented Leucaena Leaf (Leucaena leucocephala) Meal With Trichoderma sp. As Feed Ingredients to Increase on The Growth Of Green Catfish (Hemibagrus nemurus) Fingerlings - Sirait, Lestari Roindah; Adelina, Adelina; Suharman, Indra (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT The research was conducted for 56 days , the aim to determine to get percentage fermented leucaena leaf (Leucaena leucocephala) Meal with Trichoderma sp. in feed on feed efficiency. This study uses completely randomized design (CRD) with one factor, with 5 treatment levels and 3 repetitions. The test feed used in this study was artificial feed with a protein content of 35% with a percentage Utilization of FLLM namely 0%, 5%, 10%, 15% and  20%. Test feed given as much as 10% of the weight of biomass per day with the frequency of feeding threetimes throughout the day is at 08.00, 12.00 and 16.00. The fish used in this research with in 0,99 g of weight. Fish were reaered in 15 cage units (0,5x0,5x1 m3) with the stocking density 0f 20 fish/cage.  The results showed that the percentage of FLLM significant effect (P<0,05) on feed  efficiency, protein retention and specific growth rate but did not significantly affect the survival rate of green catfish fingerlings. Based on the results of this study concluded that Utilization of FLLM  15% give the best respons on the feed  efficiency, protein retention and specific growth rate.Kata Kunci : Fermented LeucaenaLeaf Meal, Hemibagrus nemurus, Growth, Trichoderma sp.